2019
DOI: 10.3390/met9060658
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of MQCL Hard Milling of SKD 11 Tool Steel Using MoS2 Nanofluid

Abstract: The present work shows an experimental investigation on the effect of minimum quantity cooling lubrication (MQCL) during hard milling of SKD 11 tool steel (52–60HRC). The novelty here lies on the use of MQCL technique, which comprises the cooling strategy based on the principle of Ranque-Hilsch vortex tube and MQL method. Moreover, MoS2 nanoparticles are suspended in MQCL based fluid to improve the lubricating character. The response parameters, including surface roughness, surface microstructure, and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The lowest values of F y occur in the concentration range of 1.0-1.25 wt% (Figures 12-13) and the cutting speed of 95-105 m/min (Figures 12-14). The cutting force F y is largest at the hardness of 54-57HRC, which is the distinguishing characteristic of hard machining and is suitable to the previous study [2,33]. The similar observation can be made with the cutting force F z , and the difference is only the level and value (Figures 15-17).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The lowest values of F y occur in the concentration range of 1.0-1.25 wt% (Figures 12-13) and the cutting speed of 95-105 m/min (Figures 12-14). The cutting force F y is largest at the hardness of 54-57HRC, which is the distinguishing characteristic of hard machining and is suitable to the previous study [2,33]. The similar observation can be made with the cutting force F z , and the difference is only the level and value (Figures 15-17).…”
Section: Resultssupporting
confidence: 68%
“…The MQCL system includes Frigid-X Sub-Zero Vortex Tool Cooling Mist System (made by Nex Flow™, compressed air, pressure stabilization device, water-based emulsion 5.0% and MoS 2 nanoparticles. The cutting forces are directly measured by Kistler quartz three-component dynamometer (9257BA) connected to A/D DQA N16210 (made by National instruments, USA), which is linked to the computer having DASYlab 10.0 software [33]. MoS 2 nanoparticles made by Luoyang Tongrun Info Technology Co., Ltd with the size of 30nm (average) were used.…”
Section: Experimental Set Upmentioning
confidence: 99%
“…The phosphonium based cation was selected due to its excellent performance in tribology, inertness to organic oil, non-corrosive nature, miscibility, anti-wear, and anti-scuffing properties [27][28][29][30][31]. Additionally, effective results of halogen-based anions were noticed in the work [14][15][16][32][33][34]. Studies by Fox and Priest suggested that similar ILs not containing fluorine were less effective as lubricants compared to hydrocarbons, especially in the reduction of wear on surfaces caused by tribo-corrosion [34].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it was visualised that an enhancement in the surface roughness of 25% related to dry machining [16]. Addition of halogen-free IL as an additive in water abridged the coefficient of friction by greater than 70% when matched to water, and attributed a trifling wear rate of aluminium [17].…”
Section: Introductionmentioning
confidence: 99%
“…It uses a small amount of cutting fluid in the form of an oil mist that is directly sprayed to the contact zone, helping to reduce friction and cutting forces, and decreasing the surface’s crumple zone by a large amount (~50%) when compared with dry cutting [ 21 ]. Consequently, MQL reduces tool wear [ 22 , 23 ]. This technique combines the lubrication from the cutting fluid and the cooling from the air pressure, sometimes reducing the thermal shock caused by flood lubrication [ 24 ], and can be used in drilling, milling, turning, and others.…”
Section: Introductionmentioning
confidence: 99%